2019
DOI: 10.1002/mbo3.981
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of provisioned and wild rhesus macaques (Macaca mulatta) living in a limestone forest in southwest Guangxi, China

Abstract: The gut microbiota plays an important role in animal health and is strongly affected by the environment. Captivity and human source food have been shown to influence drastically the gut microbiota composition and function of wild animals. Therefore, in the present study, the gut microbiota of provisioned and wild populations of limestone‐living rhesus macaques (Macaca mulatta) were compared using high‐throughput 16S rRNA sequencing and bioinformatic analyses. The results indicated that provisioned macaques had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 67 publications
(122 reference statements)
9
42
1
Order By: Relevance
“…Released individuals explore different resources (not necessarily eaten by wild primates) but keep also an alternative diet matching captivity, resulting on a mixture of bacteria from captivity, and bacteria associated with the liberation site. This is the case of macaques in the wild, that when they are given food supplies, they display a greater diversity than those in the traditional wild diet allowing them to digest new and different types of food 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Released individuals explore different resources (not necessarily eaten by wild primates) but keep also an alternative diet matching captivity, resulting on a mixture of bacteria from captivity, and bacteria associated with the liberation site. This is the case of macaques in the wild, that when they are given food supplies, they display a greater diversity than those in the traditional wild diet allowing them to digest new and different types of food 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of conservation, some of the anthropogenic disturbances that are causing the decline of primate populations (e.g., habitat degradation, captivity and food provisioning) were associated with faecal microbiota alterations [ 13 , 19 , 20 ]. The evidence of microbiota alteration by habitat degradation can be clearly seen in the case of red colobus ( Procolobus gordonorum ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed significant differences between degraded and non-degraded habitats, with significantly higher faecal microbiota diversity in non-degraded habitats [ 13 ]. On another hand, recent evidence suggests that, in tourist areas, the intake of anthropogenic food, low in fibre and high in non-structural carbohydrates, is determinantal to the microbiota of primate species [ 17 , 20 ]. Chen et al, [ 20 ] demonstrated that food provisioning modifies the gut microbiota of rhesus macaques ( Macaca mulatta ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations